Adult pancreatoblastoma: a case report. Issue 8 (August 2021) - Li, Jianchun; Peng, Chengzhong; Fan, Xiaoming; Wang, Ligang; Wang, Jing
Pancreatoblastoma (PB) is a rare epithelial malignancy usually occurring in the paediatric population. Adult PB is rare, and its imaging findings are similar to those of other tumours, making preoperative diagnosis a considerable challenge. We report correlative ultrasound, contrast-enhanced ultrasonography, contrast-enhanced magnetic resonance imaging, and positron emission tomography-computed tomography findings in a 60-year-old woman with PB. PB often presents with uncommon imaging features and should be considered in the differential diagnosis of pancreatic masses. It is important for clinicians to be aware of these differences to provide effective treatment.